2022
DOI: 10.5603/ep.a2021.0102
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of SGLT-2i in overweight/obese, non-diabetic individuals: a meta-analysis of randomized controlled trials

Abstract: may be difficult from an individual's perspective. Obesity control guidelines recommend lifestyle interventions and medication for the overweight population [5]. So far, only four kinds of anti-obesity drugs (orlistat, phentermine/topiramate, naltrexone/bupropion, and liraglutide/semaglutide) have been approved by the US Food and Drug Administration for sustained weight management [5,6]. The effectiveness of orlistat, phentermine/topiramate, and naltrexone/bupropion is limited, the safety is unknown, and the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“… 2022 ), and SGLT-2 inhibitors are associated with urinary or reproductive system infections (Shi et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“… 2022 ), and SGLT-2 inhibitors are associated with urinary or reproductive system infections (Shi et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2Is reduced weight and waist circumference in overweight or obese patients without diabetes compared with those in the control group (other drugs or placebo), according to a systematic review (13 studies) ( 29 ). The mean body weight loss due to SGLT2Is in this population was -1.62 kg compared with that in the placebo group, and the BMI decreased by -0.47 kg/m 2 , which was superior to the placebo, according to a meta-analysis (5 clinical trials) ( 30 ).…”
Section: Metabolic Dysfunctions In Patients Undergoing Antipsychotic ...mentioning
confidence: 99%
“…After 24 weeks of treatment, there were small yet statistically significant differences in waist circumference observed between the study groups (Bays et al, 2020) [4] . 2 meta-analyses have found that SGLT-2 inhibitors reduced weight in obese nondiabetic patients (Shi et al, 2022;Zheng et al, 2021) [28,32] .…”
Section: Sodium-glucose Cotransporter (Sglt) Inhibitorsmentioning
confidence: 99%